ORCHIDACEAE NOVAE VEL MINUS COGNITAE - JONES, H. G. (Research Center for Biology, 1974)
The new species Cymbidium intermedium from India is described, and critical morphological and nomentlatural notes on the AsiaticÂ Cirrho-petabtm putidmn as well as the American Hoff-mannseggella crispilabia and Encyclia fragrana are presented.